2016
DOI: 10.1002/med.21428
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2/BCRP: Specific and Nonspecific Modulators

Abstract: Multidrug resistance (MDR) in cancer cells is the development of resistance to a variety of structurally and functionally nonrelated anticancer drugs. This phenomenon has become a major obstacle to cancer chemotherapy seriously affecting the clinical outcome. MDR is associated with increased drug efflux from cells mediated by an energy-dependent mechanism involving the ATP-binding cassette (ABC) transporters, mainly P-glycoprotein (ABCB1), the MDR-associated protein-1 (ABCC1), and the breast cancer resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 198 publications
(266 reference statements)
1
51
0
Order By: Relevance
“…The main focus of ABC transporter research within the last 40 years laid mostly on the search/finding and improvement/development of inhibitors to treat MDR‐conferring cancer cells . Here again, the first discoveries concerned P‐gp, as this was the very first described ABC transporter involved in the MDR phenotype .…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of ABC transporter research within the last 40 years laid mostly on the search/finding and improvement/development of inhibitors to treat MDR‐conferring cancer cells . Here again, the first discoveries concerned P‐gp, as this was the very first described ABC transporter involved in the MDR phenotype .…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance is closely related to increased drug efflux mediated by an energy-dependent mechanism involving the ABC (ATP binding cassette) transporters, mainly ABCB1 (ATP binding cassette subfamily B member 1), ABCC1 (ATP binding cassette subfamily C member 1), and ABCG2 (ATP binding cassette subfamily G member)[24]. Moreover, it has been reported that ABCG2 plays an important role in regulating chemo-resistance in gastric cancer[22].…”
Section: Resultsmentioning
confidence: 99%
“…Driven by the hypothesis that drug resistance in the treatment of cancers could be influenced by the co‐administration of BCRP‐inhibitors, numerous compounds were tested for their ability to modulate BCRP transport functions (for a recent review, see Peña‐Solórzano, Stark, König, Sierra, & Ochoa‐Puentes, ). The most consistent results were determined with individual flavonoids, including quercetin, silymarin, daidzein and other polyphenols, as well as the natural stilbenoid resveratrol.…”
Section: Transporter Polymorphismsmentioning
confidence: 99%